Treatment Preference For Patients With Chronic Obstructive Pulmonary Disease: A Review - Agung Rejecky; Erna Rochmawati (Universitas Aisyah Pringsewu, 2022)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic illness that requires regular treatment to relieve symptoms and reduce the frequency of relapses and the severity of exacerbations. Treatment options for COPD are pharmacological and non-pharmacological therapies, and patients can prefer the type of treatment. The inhaler is one of the options for pharmacological therapy, where there are several types of inhalers, including metered dose inhalers (MDI), soft mist inhalers (SMI) and dry powder inhalers (DPI). To date, there is no synthesis on the patient's preference of treatment for COPD. The review aimed to synthesize available evidence on patients' preferences for COPD treatment. Three databases, which include PubMed, Ebsco, and Scopus, were searched using terms related to